A crop choice framework for a more sustainable agriculture, the case of the Argolid Valley in Greece - Blatsou, Condylenia (Cranfield University, 1996)
This thesis integrates a number of disciplines from the natural and social sciences to develop a crop choice framework for a “more” sustainable agriculture. The biophysical, socio-political and technoeconomic influences upon farmer’s decisions form the central component of the framework with policy makers the intended target. The sustainability of agriculture generates a lot of debate among academic and policy communities. The literature concerning this debate is considered and it is argued that sustainability is site specific and can only be discussed in relative rather than absolute terms. The research is carried out in three phases each of which contributes to the final framework. The first phase produces a generic framework which is then applied to a particular area, the Argolid Valley in the Peloponnese, Greece. The modified framework is then used to evaluate a specific “crop” (greenhouse roses) and it is demonstrated that the crop will only be adopted by a minority of farmers with particular characteristics. However, it constitutes a useful example for the assessment of whether a crop is promoting sustainability in all its social, economic, ecological and agronomic dimensions. The thesis provides an overview of the disciplinary components that a crop choice framework should include and the techniques employed to support this. Similarly, by underlining the critical role of the farmer, it aims to produce a conceptual framework which is useful for policy formulation and decision-making.